Determinan Financial Distress: A Study on The Property and Real Estate Sector in The Indonesia Stock Exchange - Marcella, Rini; Utami, Wiwik (Advances In Social Humanities Research, 2024)
The property and real estate sector plays a crucial role in the Indonesian economy but faces significant risks of financial distress. This study aims to identify the determinants of financial distress within this sector, focusing on companies listed on the Indonesia Stock Exchange between 2018 and 2022. The research examines the effects of profitability, liquidity, leverage, interest rates, and inflation on financial distress. Using a quantitative approach, this study applies statistical techniques and regression analysis to secondary data from various property and real estate companies. The findings reveal that: (i) profitability has a negative impact on financial distress, indicating that lower profitability increases the likelihood of financial difficulties; (ii) liquidity also shows a negative relationship with financial distress, meaning reduced liquidity elevates financial risk; (iii) leverage negatively influences financial distress, suggesting that higher debt levels exacerbate financial instability; (iv) rising interest rates contribute to financial distress by increasing borrowing costs, thereby straining company resources; and (v) inflation worsens financial distress by eroding purchasing power and dampening property demand. This study provides valuable insights for stakeholders, including investors and policymakers, to enhance their understanding of financial risk management in the property and real estate sector. The novelty of this research lies in its specific focus on a critical period and sector within the Indonesian economic landscape, addressing key areas of concern for financial stability